'We struggle and muddle.' A qualitative study exploring community ABI therapists' experiences of using, training in and implementing behaviour interventions. Issue 1 (4th March 2021) - Carmichael, Jai Jason; Hicks, Amelia J.; Gould, Kate Rachel; Feeney, Timothy J.; Analytis, Penelope; Ponsford, Jennie Louise
Abstract: Objectives: Individuals with acquired brain injury (ABI) may present with challenging behaviours (CB) that place themselves and others at risk of harm and impact their community integration. It is crucial for community ABI therapists to successfully train in and implement behaviour interventions. The current study aimed to investigate community ABI therapists' experiences of using, training in and implementing behaviour interventions. An additional aim was to determine these therapists' understanding of Positive Behaviour Support (PBS), one approach to addressing CB with a focus on improving quality of life. Methods: Semi-structured interviews were conducted with 24 Australian community ABI therapists about their experiences of using, training in and implementing behaviour interventions and understanding of PBS. Inductive thematic analysis and content analysis were performed on interview transcripts. Findings: The thematic analysis resulted in the generation of six themes which described the difficulties participants faced in training in and delivering behaviour interventions and identified their training and implementation needs. The content analysis resulted in 10 categories that characterised participants' understanding of PBS, which centred around the absence of consequences, a focus on antecedents, person-centred practice and encouraging prosocial alternatives to CB. Conclusions: The findings highlight a need and desire for more practical and interactive clinician training in behaviour interventions for individuals with ABI. Moreover, the findings suggest a limited understanding of PBS amongst community ABI therapists. Important considerations for the development of clinician training in ABI behaviour interventions and subsequent implementation into community practice are discussed.